The treatment modalities and outcomes of recurrent nasopharyngeal carcinoma: a retrospective cohort study in the modern era - Chien, Ju-Chun; Huang, Chien-Yu; Hu, Yu-Chang; Chang, Kuo-Chen; Chang, Kuo-Ping; Kang, Bor-Hwang; Liu, Wen-Shan (Therapeutic Radiology and Oncology, 2019)
Background: While chemoradiotherapy being widely recognized as primary treatment for nasopharyngeal carcinoma (NPC), optimal salvage modalities for locoregionally recurrent NPC (LRrNPC) are still under debate. This study aimed to explore outcomes of different salvage modalities for LRrNPC. Methods: Non-metastatic LRrNPCs were retrospectively recruited. Clinical factors and salvage treatments were evaluated. The primary and secondary endpoint were locoregional-progression-free survival (LRPFS) and overall survival (OS), respectively. Outcomes were compared among re-irradiation (reRT), surgical resection (SR), combination therapy (SR + reRT), and systemic treatment only (STx). Results: From 2006–2017, 29 consecutive LRrNPCs were enrolled, including 37.9% rT1-2 and 62.1% rT3-4 diseases. Salvage treatments included 14 reRT, 6 SR, 6 SR + reRT, and 3 STx. All re-irradiations were intensity-modulated radiotherapy (IMRT) and 83.3% SRs were done by endoscopic approach. After median follow-up of 36 months, the 3-year LRPFS was 56.5% and 3-year OS was 64.1%. When compared to STx, reRT and SR + reRT both showed superior LRPFS (re-RT, HR: 0.06, P=0.009; SR + reRT, HR: 0.07, P=0.021, adjusted for rT), while SR revealed no significant benefit. However, there was no significant difference in LRPFS among the three local treatment modalities. Severe complication rates were 51.7% for ≥grade 3 and 6.9% for grade 5. Conclusions: For LRrNPCs, locoregional treatments including reRT and SR + reRT might have additional local control benefit from systemic therapy. The risk of fatal toxicity decreased with increasing use of IMRT and endoscopic resection. Considering the limited case number and retrospective design, prospective trials are warranted to further evaluate the efficacy and safety.